Depression, Anxiety, and Suicidal Ideation in Chinese University Students During the COVID-19 Pandemic - Zhou, Shuang-Jiang; Wang, Lei-Lei; Qi, Meng; Yang, Xing-Jie; Gao, Lan; Zhang, Suo-Yuan; Zhang, Li-Gang; Yang, Rui; Chen, Jing-Xu (Frontiers in Psychology, 2021)
Coronavirus disease-2019 (COVID-19) pandemic has seriously threatened the global public health security and caused a series of mental health problem. Current research focuses mainly on mental health status and related factors in the COVID-19 pandemic among Chinese university students. Data from 11133 participants was obtained through an online survey. The Patient Health Question-9 (PHQ-9) was used to assess depressive symptoms, the Social Support Rate Scale (SSRS) was used to assess social support. We also used 7-item Generalized Anxiety Disorder Scale (GAD-7) assess anxiety symptoms. In total, 37.0% of the subjects were experiencing depressive symptoms, 24.9% anxiety symptoms, 20.9% comorbid depressive and anxiety symptoms, and 7.3% suicidal ideation. Multivariable logistic regression analysis revealed an increased presence of mental health problems in female students, graduate students, and those with personal COVID-19 exposure. Awareness of COVID-19, living with family were protective factors that reduced anxiety and depression symptoms, In addition, male, personal COVID-19 exposure, depressive and anxiety symptoms were risk factors for suicidal ideation. Social support, COVID-19 prevention and control measures, prediction of COVID-19 trends, living with family and graduate students are protective factors for reducing suicidal ideation.